Observation of Topological Nodal-Ring Phonons in Monolayer Hexagonal Boron Nitride - Tao, Zhiyu; Wang, Yani; He, Shuyi; Li, Jiade; Xue, Siwei; Su, Zhibin; Sun, Jiatao; Peng, Hailin; Guo, Jiandong; Zhu, Xuetao (Chinese physics letters, 2025)
Topological physics has evolved from its initial focus on fermionic systems to the exploration of bosonic systems, particularly phononic excitations in crystalline materials. Two-dimensional (2D) topological phonons emerge as promising candidates for future technological applications. Currently, experimental verification of 2D topological phonons has remained exclusively limited to graphene, a constraint that hinders their applications in phononic devices. Here, we report experimental evidence of topological phonons in monolayer hexagonal boron nitride using advanced high-resolution electron energy loss spectroscopy. Our high-precision measurements explicitly demonstrate two topological nodal rings in monolayer hexagonal boron nitride, protected by mirror symmetry, expanding the paradigm of 2D topological phonons beyond graphene. This research not only deepens fundamental understanding of 2D topological phonons, but also establishes a phononic device platform based on wide-bandgap insulators, crucial for advancements in electronics and photonics applications.